Flu vaccination coverage among healthcare workers: a comparison between 2018 and 2019 campaigns. (30th September 2020) - Varadi, G; Vacchi, O G B; Moretti, V; Pozzi, D; Chirico, L; Del Pin, M; Brunelli, L; Cocconi, R; Brusaferro, S
Abstract: Background: In Italy, recommended annual influenza vaccination is free to healthcare workers (HCWs) to prevent flu spread. No official data are available on HCWs' vaccination coverage (VC), which minimum target is set at 75%. Aim of this study is to compare 2019-20 and 2018-19 flu vaccination coverage in order to evaluate last year campaign effectiveness. Methods: 2019-20 flu vaccination campaign efforts at Udine Hospital (Italy) were improved with the aid of public health residents to tackle HCWs convenience concerns. From October 29th to December 5th 2019, dedicated areas and days were increased, informative course about influenza vaccination (efficacy, benefits and safety) toward HCWs were conducted. Data about HCWs getting their flu shot within the hospital were traced and analyzed, grouping different categories. Results: During 2019-20 flu season, vaccinated HCWs were 29.1% (1, 169/4, 012), while they were 22.7% (955/4, 203) in 2018-19 (p < 0.0001). The 2019-20 campaign resulted to be effective among doctors (45.0% vs 38.4%; p = 0.0132), residents (52.4% vs 40.7%; p = 0.0003) and nurses (24.1% vs 17.3%; p < 0.0001). The less compliant category was midwives, who maintained the worse vaccination coverage in both seasons (20.4% and 24.1%; p = 0.6555). Regarding other HCWs in 2019-20, 18.6% were vaccinated (in 2018-19 14.0%, p = 0.002). Conclusions: A significant improvement in vaccination coverage during 2019-20 flu season was reached by the specific vaccination campaign for all categories except midwives. Despite this, the global vaccination coverage is still far from the desired target and more must be done to fill this gap. Evidence of HCWs categories for which this intervention was more effective, could be useful in planning next flu vaccination strategies. Key messages: Continuous efforts made by public health professionals in promoting flu vaccination show their effect on healthcare workers flu shot adherence. A planned vaccination agenda and educative course about influenza infection and benefits of vaccination, seem to be good strategies to improve vaccination coverage.